Comparing the Effect of Open-Ended and Scientific Approaches on Elementary School Students’ Mathematical Connection Skills - Martines; Prabawanto, S. (International Conference on Elementary Education, 2022)
Mathematical connection ability is one of the most important basic mathematical abilities. However, several reports indicate that students' mathematical connection skills are still weak and for this reason it is necessary to enhance the students' ability. The ability is necesary to prepare students to meet the global era and various situations in daily life. To enhanche the mathematical connection skills, it is necessary to apply an appropriate teaching approach, namely the open-ended and the scientific approach. This study aims to describe the comparison of the effect of teaching with an open-ended and a scientific approach on enhancing students' mathematical connection abilities. This study was a quantitative study with a pre-test post-test control design. The participants were the 4th-grade students from class IV A (treated using an open-ended approach) and from class IV C (treated using a scientific approach). The study found that open-ended and scientific approaches affected students’ mathematical connection skills by 60.5% and 76.7%, respectively. This result show that the open-ended and the scientific approach give a positive effect on enhancement of students' mathematical connection skills. However, the scientific approach was found to exhibit a better effect than the open-ended approach.